2018
DOI: 10.1002/jcb.27927
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine inhibits melanoma cell proliferation by regulating ERK phosphorylation

Abstract: The melanoma is responsible for the majority of all skin cancer–related deaths worldwide. Evidence suggests that local anesthetics provide some benefit in the treatment of cancer via inhibition of cellular proliferation, invasion and migration. However, the potential antiproliferative effects of local anesthetics in the treatment of melanoma remain to be elucidated. In this study, we investigated the antiproliferative effects and underlying mechanism of the commonly used local anesthetic (lidocaine) on melanom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 21 publications
1
27
0
2
Order By: Relevance
“…These two signalling pathways are also in charge of the growth and metastasis of human cancers, including lung cancer [32]. The inhibitory effects of lidocaine on the activation of ERK and PI3K/AKT pathways have been found in melanoma cells [26,33]. However, only one literature indicated the effects of lidocaine on PI3K/AKT signalling in lung cancer cells [13].…”
Section: Discussionmentioning
confidence: 99%
“…These two signalling pathways are also in charge of the growth and metastasis of human cancers, including lung cancer [32]. The inhibitory effects of lidocaine on the activation of ERK and PI3K/AKT pathways have been found in melanoma cells [26,33]. However, only one literature indicated the effects of lidocaine on PI3K/AKT signalling in lung cancer cells [13].…”
Section: Discussionmentioning
confidence: 99%
“…Although the anticancer efficacies can be confirmed in various cancers, its exact mechanisms/targets remain unclear. As summarized in Table 1 and Figure 2 , the reported targets/mechanisms include MMP-9 ( Piegeler et al, 2015 ), ERK ( Chen et al, 2019 ), TRPV6 ( Jiang et al, 2016 ), and VEGF/VEGFR2 ( Gao et al, 2019 ), as well as the regulation of epigenetics ( Li et al, 2014 ), mi-RNA ( Qu et al, 2018 ; Sui et al, 2019 ; Yang Q. et al, 2019 ), inhibition of metastasis ( D’Agostino et al, 2018 ; Johnson et al, 2018 ; Sun and Sun, 2019 ), inhibition of inflammation ( Freeman et al, 2019 ), impacting mitochondrial metabolism ( Okamoto et al, 2017 ; Gong et al, 2018 ), the regulation of reactive oxygen species (ROS) ( Okamoto et al, 2016 ), etc. Importantly, as an ion channel regulator, lidocaine may exert its anticancer effects via regulation of other channels or membrane potential, such as mitochondrial membrane potential (MMP), which may lead to the decrease of MMP, finally resulting in the mitochondria-related apoptosis ( Li et al, 2014 ; Lu et al, 2016 ; Ye L. et al, 2019 ), providing valuable information for its targets identification.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Another study conducted by Chen et al showed that lidocaine (0.1, 3, and 5 mM, as determined by cell-counting kit-8 reagent) could kill A375 melanoma cells and suppress the colony formation in a concentration-dependent manner via cell cycle arrest at G1 phase ( Chen et al, 2019 ). These effects were mediated by the down-regulation of Ki-67, a protein associated with cell proliferation and the cell division cycle ( Robinson et al, 2018 ; Su and Chen, 2019 ), and down-regulation of phosphorylation of ERK.…”
Section: Lidocaine In Cancer Treatmentmentioning
confidence: 99%
“…Many preclinical studies also revealed the mechanism underlying the effects of local anesthetics on cancer cells [6]. Several pathways were reported to be involved in the effect of local anesthetics on cancer cells, including the Wnt/βcatenin pathway [7], the apoptosis pathway [8], the MAPK/ERK pathway [9,10], REDOX pathway [11], RhoA/ROCK/ MLC pathway [12] and so on. Certain growth factors [13] or regulating molecular [14] were also through to be targeted by lidocaine.…”
Section: Pharmacological Mechanisms Of Local Anesthetics On Cancermentioning
confidence: 99%